Origin of deep carbonate reservoir in northeastern Sichuan Basin: New insights from in-situ hydrothermal diamond anvil cell experiments - Zhang, Shan-ming; Liu, Bo; Qin, Shan; Zhang, Xue-feng; Tian, Yong-jing; Guo, Rong-tao; Liu, Jian-qiang (Journal of Central South University, 2017)
In situ Raman analysis on the segregated near-equilibrium carbonate-fluid interaction at elevated temperatures (room temperature−260 °C) and pressures (13-812 MPa) in a hydrothermal diamond anvil cell (HDAC) reveals the preservation mechanism of porosity in deep carbonate reservoirs in the northeastern Sichuan Basin. The carbonate-fluid interaction was investigated by separately heating carbonate minerals and rocks with four different acid solutions (saturated CO 2 and H 2 S solutions, HCl, CH 3 COOH) in a sealed sample chamber. A minor continuous precipitation with increasing temperatures and pressures was observed during the experiments which caused minor sample volume change. The closed system is a preservation of pores and burial dissolution may not be the dominant diagenesis in the origin of porosity. Thin section photomicrographs observations in Changxing and Feixianguan Formations demonstrate that eogenetic pores such as moldic or intragranular pores with late small euhedral minerals, intergranular, intercrystal and biological cavity pores are the main pore types for the reservoirs. Early fast deep burial makes the porous carbonate sediments get into the closed system as soon as possible and preserves the pores created in the early diagenetic stage to make significant contribution to the deep reservoir quality. The anomalous high porosity at a given depth may come from the inheritance of primary pores and eogenetic porosity is fundamental to carbonate reservoir development. The favorable factors for deep reservoir origin include durable meteoric leaching, early fast deep burial, early dolomitization, etc. This deep pores preservation mechanism may be of great importance to the further exploration in deep carbonate reservoirs in the northeastern Sichuan Basin.